Frequency and potential risk factors of polyneuropathy in transfusion-dependent Β-thalassemia major patients: a cross-sectional study - Amr I. Risha; Mervat A. Hesham; Usama R. Elsafy; Yosria A. El Taweel; Mohammed M. Omar; Sara F. Saadawy; Diana Hanna (SpringerOpen, 2024)
Abstract Background Neurological complications, including peripheral polyneuropathy, have been reported in β-thalassemia patients that negatively impact their quality of life. Chronic hypoxia, iron overload, average age, and iron chelators-induced neurotoxicity might contribute to the development of neuropathy. However, the leading offender of this complication remains not clear. We aimed to study the frequency and potential risk factors of polyneuropathy in β-thalassemia patients. We performed a cross-section study on 150 transfusion-dependent β-thalassemia major patients with a mean age of 16.44 ± 3.32 years. We performed electrophysiological studies for motor and sensory nerves. Results We found that 31.3% of cases had neurological manifestations with significant relation to age, duration of the disease, and frequent transfusion. Out of 47 patients with neurological manifestations, 12 (25.5%) had abnormal nerve conduction velocity (NCV). Abnormal median, peroneal, and tibial nerve motor amplitudes were detected in 10.6%, 10.6%, and 14.9% of patients respectively. Abnormal median, peroneal, and sural nerve sensory amplitudes were detected in 4.3%, 2.2%, and 10.6% of patients respectively. Apart from a significant relation between abnormal NCV and older ages, no significant relation was detected with other studied clinical and laboratory parameters. Conclusion We detected a high frequency of motor and sensory polyneuropathy in B-thalassemia patients. Polyneuropathy was predominately detected in older ages highlighting that neuropathy in thalassemia patients is probably age-dependent. Other factors including disease duration, transfusion frequency, and iron overload might have a contributing effect, however, that could not be confirmed in this study. Further studies are needed to verify the frequency and predictors of polyneuropathy in B-thalassemia patients.